Analisis Kesantunan Berbahasa dalam Realisasi Tuturan Cawokah Masyarakat Sunda - Triyanto Triyanto (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
Speech in humor can be found in various cultures, including Sundanese culture. Sundanese culture controls humor as a content that cannot be separated from everyday speech. One of the humor that often colors the speech is cawokah, which is a style of humor that raises the theme of marriage and genitals but is packaged implicitly. The results of this study elaborated on the cawokah that has been analyzed by using the theory of politeness strategy. In the analysis of politeness strategy, each speech will be analyzed by using Saving Face theory. This theory analyzed utterance and its honor that is attached to each individual. This approach is intended to find out the purpose of the realization of each speech. Then it was known that the purpose of the realization of the cawokah utterance was mostly intended as facial glorification and a small part was intended as facial contempt.